Uji Aktivitas Antidiabetes Ekstrak Etanol Akar Kabau (Archidendron bubalinum (Jack) I.C. Nielsen) terhadap Tikus Putih Jantan yang Diinduksi Diet Tinggi Lemak dan Fruktosa - Annisa Amriani S; Fitrya Fitrya; Rennie Puspa Novita; Dapid Caniago (Jurnal Penelitian Sains, 2021)
The purpose of this research to study the antidiabetic activity of extract in type 2 diabetes mellitus rats induced by high fat and fructose diet. Induction is done by giving fructose 1800 mg/kgBW and high fat (15% pork oil and 5% duck egg yolk) 15 g/rat for 30 days. Male Wistar albino rats are used as animal models which divide into 6 group, normal (aquadest), negative control (Na CMC 0,5%), positive control (Metformin 151,20 mg/kgBW), and 3 test (ethanol extract of kabau root 100, 200, and 400 mg/kgBW). Preprandial blood glucose levels are measured using DTN-410-K photometer, on day 0, 30, 35, 40, and 45. The result of AUC30-45 and percentage of decreasing blood glucose level for positive control group are 1727,01 and 73,29%, and 3 test group (100 mg/kgBW, 200 mg/kgBW, dan 400 mg/kgBW) are 1893,32 and 43,50%; 1849,14 and 51,41%; 1789,15 and 62,16%. This point indicate that ethanol extract of kabau root has an antidiabetic activity and there is no significant difference compared with metformin (p>0,05). According to the relation between percentage of blood glucose level with dose, value of ED50 is 194,64 mg/kgBW. Keywords: ethanol extract, kabau root, antidiabetic, high fat and fructose diet